(3GdLOjO aj GdbhGYO hGdGYQGa GdehMOI GdGYJeGOGJ GdeSJfOjI (B500 /s - (3GdUZjQ MSGe GdOjf, YHO GdZfjs ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2003)
(3GdbhGYO GdLOjOI daMU GdeSJfOGJ h eWGHbJgG (B- (3GdeYGdLI GdJaUjdjI deSJfOGJ fbd GdHVGYI (B- (3GdGMcGe GdJj GSJMOKJgG GdbhGYO h GdGYQGa GdehMOI (B- (3GdGMcGe GdeSJMOKI deUdMI GdeSJajOs
(3HHdjhZQGajG(B: 147(3U(B. (3GdedGMb(B: 135(3U(B.s